Partisan politics in the global economy - Garrett, Geoffrey, 1958- (Cambridge University Press, 1998)
This book is about: Politics, Policy, and Performance; Market Integration and Domestic Politics; Economic Policy; Economic Performance; and The 1990s and Beyond.